2022
DOI: 10.1149/1945-7111/ac6833
|View full text |Cite
|
Sign up to set email alerts
|

Operando Ultrasonic Monitoring of Lithium-Ion Battery Temperature and Behaviour at Different Cycling Rates and under Drive Cycle Conditions

Abstract: Effective diagnostic techniques for Li-ion batteries are vital to ensure that they operate in the required voltage and temperature window to prevent premature degradation and failure. Ultrasonic analysis has been gaining significant attention as a low cost, fast, non-destructive, operando technique for assessing the state-of-charge and state-of-health of Li-ion batteries. Thus far, the majority of studies have focused on a single C-rate at relatively low charge and discharge currents, and as such the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…At a higher C-rate, the battery internal temperature might be raised significantly, and it is important to understand the effects of increased in situ internal temperature on the ultrasonic wave. 13 The experimental setup of ultrasonic measurements on the cylindrical lithium-ion battery was kept inside the temperaturecontrolled chamber. The battery was tested at three different SoCs: 0%, 50%, and 100%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a higher C-rate, the battery internal temperature might be raised significantly, and it is important to understand the effects of increased in situ internal temperature on the ultrasonic wave. 13 The experimental setup of ultrasonic measurements on the cylindrical lithium-ion battery was kept inside the temperaturecontrolled chamber. The battery was tested at three different SoCs: 0%, 50%, and 100%.…”
Section: Resultsmentioning
confidence: 99%
“…5 Ultrasonic diagnostic technology has widely been used for nondestructive evaluation of material properties and structural health monitoring and has recently been applied in numerous studies on the SoH characterization and evaluation of lithium-ion batteries as a cost-effective and rapid method that can also be used for in-operando measurement. [13][14][15][16][17][18][19][20] The ultrasound diagnostic technique is based primarily on the recorded signals of ultrasound propagation in the testing medium to derive the appropriate characteristics of the medium. In ultrasound measurements, the stress wave excited by the transmitter propagates in the material medium and is received by the receiver.…”
mentioning
confidence: 99%
“…The acoustic technique is regarded as a low-cost and rapid probe to identify the initial gas distribution and other defects within a pouch cell. 40 The previous section showed that Li-ion cells, operated in different orientations inside the pack, displayed distinct variations in their associated acoustic maps, thought to be associated with areas of internal cell degradation. Macro-CT scans were performed on the representative samples at the corner opposite the tabs; namely Pristine, rotated-aged (R2) and flataged (F3) samples.…”
Section: X-ray Ct Measurementsmentioning
confidence: 97%
“…For consistency, a specific ToF range was selected for all cells, chosen because it is where the part of the waveform, known as the 'echo-peak', is located. 40 The echo-peak is useful to monitor as it is where the waveform has travelled the whole way through the cell and reflected from the back surface, so characterising the entire cell. The maximum amplitude of the ultrasonic signal within this ToF range, at each point, are combined to produce a colour map.…”
Section: Ultrasonic Mapping Measurement Proceduresmentioning
confidence: 99%
“…26 Recently, data reported by this group has shown that the technique can be used to monitor the temperature of a cell during operation. 27 Due to the penetrative nature of the ultrasound signal used for the measurement, heating at any point within the cell should be detectable and achievable within microseconds. Some limitations are still associated with the use of ultrasonic monitoring of LIBs, a deeper understanding of the technique is required with both the degradation and SoC estimations resulting in time of flight shifts.…”
mentioning
confidence: 99%